Using Enstrophy-Based Diagnostics in an Ensemble for Two Blocking Events - Andrew D. Jensen; Anthony R. Lupo (Advances in Meteorology)
Recent research has used enstrophy-based diagnostics to identify the development and dissipation stages of blocking events. These previous studies made use of reanalysis data sets in the calculations of the enstrophy-based diagnostics, such as the NCEP-NCAR reanalysis (2.5° × 2.5°) of geopotential height and horizontal winds. However, none of these studies has explored the use of the enstrophy-based diagnostics in weather or climate models with higher horizontal resolution. In this paper, the enstrophy-based diagnostics are used to analyze two blocking events, using data from the ERA-Interim reanalysis data set (0.75° × 0.75°) and also the Global Ensemble Forecast System (GEFS) (1° × 1°). The results of this work indicate that using an ensemble may be more effective than a single dynamical control forecast in evaluating the enstrophy-based diagnostic quantities, and that the results are similar to those obtained with coarser resolution.